Diode Laser Excision of Focal Epithelial Hyperplasia (Heck’s Disease): A Case Report: Laser Excision of Focal Epithelial Hyperplasia - Sarabadani, Javad; Chiniforush, Nasim; Yazdandoust, Yasaman (Journal of Lasers in Medical Sciences, 2022)
Introduction: Focal epithelial hyperplasia (FEH), also known as Heck’s disease, is a human papilloma virus-induced proliferation of epithelial cells, which causes asymptomatic lesions in the oral mucosa. Heck’s disease is more prevalent among children or in a family. Despite the self-limitation of lesions, they may progress or cause esthetical and functional discomforts. Hence, early diagnosis is necessary. Case Presentation: A middle-aged man with peripheral multiple soft, elevated, sessile, smooth, lobulated surface and nodular lesions in his right buccal mucosa was referred. The dimensions of the lesions varied from 5 to 25 mm. Through clinical and histopathological examinations, Heck’s disease was diagnosed. The diode laser (wavelengths of 980 nm), 1-W power using continuous waves) was applied serially (in 2 sessions with a 1-week interval) for surgically removing the lesions. The patient was followed up for 6 months with no lesion recurrence, and gradual healing was observed. Conclusion: The laser is an effective treatment with no scar remaining after the procedure and brings satisfaction to patients. Doi:10.34172/jlms.2022.06.